The Role of Innate Immunity against Mycobacterium Leprae: A Systematic Literature Review - Putra, Reza Agustiantwo (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Innate immunity is the body's defense system that exists from birth and is the body's first defense against infection. This system involves multiple defense mechanisms that work together to recognize, deter, and respond to pathogens such as bacteria, viruses, and fungi. In the context of Mycobacterium leprae, the role of the innate immune system is very important because this bacterium has unique pathogenic properties and is capable of infecting human body cells in complex ways. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the role of innate immunity against Mycobacterium leprae. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Results: One of the main aspects of the role of the innate immune system against Mycobacterium leprae is the recognition of this pathogen by phagocytic cells, such as macrophages. Mycobacterium leprae evades recognition and destruction by these cells in a number of ways, including cell surface modification of the immune response. Conclusion: The innate immunity response plays a significant role in the response to Mycobacterium leprae infection. Innate immunity acts as an initial and fast response to mitigate the Mycobacterium leprae infection from getting more massive.